The Influence of Attitude and Desire Towards Intention To Use Online Food Delivery - Ramba, Zelia Joanna Aurelia; Pratomo, Luki Adiati (Devotion : Journal of Research and Community Service, 2024)
This research aims to analyze the influence of perceived usefulness, perceived ease of use, perceived convenience towards attitude then influence the desire and intention to use online food delivery application. The data collection techmique method uses non probability sampling with purposive sampling with google form questionnaire. Data were collected form 210 respondents with criteria of having used online food delivery applications for at least the last three months. The questionnaire with google form which contains 21 statement indicators based on a five-point Likert scale. The analytical method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS). The result showed that perceived usefulness had a positive effect on attitude, perceived ease of use had a positive effect on attitude, but perceived convenience had no effect on attitude. Attitude then had positive effect on desire and desire had a positive effect on intention to use online food delivery. The managerial implication of this research is to evaluate the online food delivery application to continue to improve the usability and ease of application for customers.